The maximal mechanical capabilities of leg extensors muscles to generate velocity and power improve at altitude - Garcia-Ramos, A.; Štirn, I.; Padial, P.; Argüelles-Cienfuegos, J.; De La Fuente, B.; Strojnik, V.; Feriche, B. (The Journal of Strength and Conditioning Research, 2018)
This study aimed (a) to analyze the effect of an acute exposure to terrestrial altitude on the force-velocity relationship parameters (maximum force [F 0], maximum velocity [V 0], and maximum power [P 0]) during a loaded squat jump (SJ), and (b) to compare unloaded SJ and countermovement jump (CMJ) performance between sea level and altitude conditions. Seventeen international swimmers were tested at sea level (295 m asl) and 7 days later at terrestrial altitude (2,320 m asl) during their first 24 hours of altitude exposure. The maximum values of force and velocity were recorded during a loaded SJ (25-100% of body weight) to determine F 0, V 0, and P 0 parameters. Inconsequential differences between environmental conditions were found for F 0 (p = 0.993, 0.02%). However, V 0 (p = 0.038, 7.6%) and P 0 (p = 0.004, 6.8%) were higher at altitude. Peak values of force (SJ: p = 0.420, 1.19%; CMJ: p = 0.010, 3.6%), power (SJ: p = 0.028, 3.5%; CMJ: p = 0.005, 3.82%), and take-off velocity (SJ: p = 0.071, 1.6%; CMJ: p = 0.009, 1.9%) recorded during the SJ and CMJ were also higher at altitude. These results highlight the potential effect of an acute exposure to terrestrial altitude on enhancing vertical jump performance. The increase in maximal power of the leg muscles at altitude is caused by an improvement in the theoretical maximal velocity at which lower limbs can extend with no significant changes in the theoretical maximal force.